Earning Management dan Deferred Tax - Setiadi Alim Lim (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2010)
Corporate managers often face conflicting interest when they report their earning for financial and tax purposes. On one side, managers desire to increase earnings that will be reported to creditors, shareholders and other external users. But on other side, managers also desire to decrease taxable income that will be reported to tax authorities. Managers can achieve these two goals by manipulating earnings upward for financial reporting but not for tax reporting. So managers don't pay income taxes on the upward earnings. In long term this will increase gap between book-tax income differences and effect deferred tax account.